Challenges and solutions for the implementation of computer-based test learning evaluation at SMKN 2 Bandung - Azzahra Putri Imanda; Dea Apriliyani; Dewi Allyya Suci Putri Anjani (Curricula: Journal of Curriculum Development, 2024)
This article explores the implementation of Computer-Based Testing (CBT) as a summative assessment method at SMK Negeri 2 Bandung, aiming for success and sustained benefits in the Indonesian education system. CBT includes diverse question formats, from multiple-choice to interactive simulations. The research objectives are: (1) describing CBT planning as a learning evaluation, (2) explaining CBT execution to enhance students' honesty in final exams at SMKN 2 Bandung, and (3) analyzing CBT results as a learning evaluation of students' honesty. This study delves into dimensions, context, and meanings related to the research subject using a qualitative approach with a descriptive method through interviews and surveys. Descriptive methods outline emerging characteristics and behaviors in the research context. This research enriches understanding of Information and Communication Technology's (ICT) role in educational transformation and proposes effective learning evaluation measures leveraging technology. The integration of CBT reflects a progressive step toward advancing education assessment methodologies.